1972
DOI: 10.1073/pnas.69.6.1416
|View full text |Cite
|
Sign up to set email alerts
|

Variable Decay of Memory and Its Recovery in Cycloheximide-Treated Mice

Abstract: Mice were trained in an automated visualdiscrimination task. When injected with cycloheximide before training, mice showed: (a) some impairment of memory within minutes after the beginning of training, (b) gradual development of total amnesia in less than 3 hr or in more than 6 hr after training, depending on the extent of training, and (c) spontaneous recovery of memory within 3 days after training. The results are consistent with the operation of three processes of memory storage: (i) a short-term process th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0

Year Published

1973
1973
2008
2008

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(64 citation statements)
references
References 19 publications
(24 reference statements)
4
60
0
Order By: Relevance
“…Gold 2006). For example, in studies using cycloheximide or anisomycin to inhibit protein synthesis, the range of times to onset of amnesia range from ∼1 h to 24 h for memory (Quartermain and McEwen 1970;Squire and Barondes 1972) and for decay of long-term potentiation range from ∼10 min to 4 h (Huang et al 1994;Tang et al 1999;cf. Gold 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Gold 2006). For example, in studies using cycloheximide or anisomycin to inhibit protein synthesis, the range of times to onset of amnesia range from ∼1 h to 24 h for memory (Quartermain and McEwen 1970;Squire and Barondes 1972) and for decay of long-term potentiation range from ∼10 min to 4 h (Huang et al 1994;Tang et al 1999;cf. Gold 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Three injections of Ani produced significant amnesia in all four training conditions; nearly all animals were amnestic under Conditions I and II. (13) " "…”
Section: Methodsmentioning
confidence: 99%
“…The discrepancy in the relative effectiveness of the two drugs, pretraining versus posttraining, suggests that Cyclo when administered prior to training caused some impairment of acquisition in addition to blocking memory formation. Squire and Barondes [ 13] have reported that Cyclo impaired acquisition of an active avoidance task in mice. The amnesia caused by a posttraining injection of Cyclo (when it could not have interfered with training) demonstrated that Cyclo is a powerful amnestic agent (Experiment 4).…”
Section: Comparison Of Ani and Cyclomentioning
confidence: 99%
“…While the,agents Cycloheximide (2,4,7,8,9) and Acetoxycycloheximide (1,3) have frequently been employed in such studies, we have found Anisomycin (5,6) to be particularly useful for b/o reasons: (a) the duration of inhibition of protein synthesis in mouse brain can be controlled by giving successive injections of Anisomycin (Ani) at 2-hr intervals (5), and (b) an injection that produces about 2 hrs of in --hibition at 80% or greater --or even a series of such injections --is far below the lethal dose of the drug (5). The degree of amnesia has been found to depend upon both the duration of inhibition and several parameters of the passive-avoidance training situation (shock intensity and latenci~s to enter and to escape the training box)j…”
mentioning
confidence: 99%